2017
DOI: 10.1186/s13223-017-0189-6
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for food allergen labeling

Abstract: BackgroundFood allergen labeling is an important tool to reduce risk of exposure and prevent anaphylaxis for individuals with food allergies. Health Canada released a Canadian food allergen labeling regulation (2008) and subsequent update (2012) suggesting that research is needed to guide further iterations of the regulation to improve food allergen labeling and reduce risk of exposure.ObjectiveThe primary objective of this study was to examine consumer preferences in food labeling for allergy avoidance and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
0
25
0
3
Order By: Relevance
“…These results are consistent with the current regulations of Argentina and Ecuador, which enforce the use of the statement “contains” in capital letters (Ecuador) or special typography (capital letters, bold letters, or different colors than the label (Argentina) [ 18 , 21 ]. Although previous studies highlighted that using symbols in combination with word-based allergen labelling statements can be more effective for communicating with food-allergic individuals than using word-based labelling only [ 29 , 30 ], no Latin American regulations for food allergen labelling enforce the use of symbols for such a purpose. The use of symbols in food allergen labelling could, perhaps, reduce the extra time that food-allergic individuals spend identifying suitable foods.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the current regulations of Argentina and Ecuador, which enforce the use of the statement “contains” in capital letters (Ecuador) or special typography (capital letters, bold letters, or different colors than the label (Argentina) [ 18 , 21 ]. Although previous studies highlighted that using symbols in combination with word-based allergen labelling statements can be more effective for communicating with food-allergic individuals than using word-based labelling only [ 29 , 30 ], no Latin American regulations for food allergen labelling enforce the use of symbols for such a purpose. The use of symbols in food allergen labelling could, perhaps, reduce the extra time that food-allergic individuals spend identifying suitable foods.…”
Section: Discussionmentioning
confidence: 99%
“…Trust as a concept has been extensively studied in relation to consumer perceptions of food safety, and food risk management in general. Consumer trust in different actors and institutions responsible for guaranteeing and controlling food safety, as well as trust in the information provided by different information sources that communicate about food safety or food‐related risks, is considered to be important for consumer confidence in the safety of food . To assess the association feeling/attitude variables on quantitative assessment and ‘trust in a product if a quantitative risk assessment (QRA) had been carried out’, we carried out a hierarchical multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer trust in different actors and institutions responsible for guaranteeing and controlling food safety, as well as trust in the information provided by different information sources that communicate about food safety or food-related risks, is considered to be important for consumer confidence in the safety of food. [38][39][40] To assess the association feeling/attitude variables on quantitative assessment and 'trust in a product if a quantitative risk assessment (QRA) had been carried out', we carried out a hierarchical multiple regression analysis. Our findings showed that perception of safety, anxiety, convenience, choice and understanding would be positively impacted when making purchasing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, food product labels play a significant role in providing consumers with adequate nutrition-related information, which facilitates making healthy and safe choices when buying food products [30]. Food allergen labeling is also an important tool in reducing the risk of exposure and in preventing anaphylaxis for individuals with food allergies [31]. It is especially important in case of masked Immunoreactivity of extracts obtained from soy seed isolates with the highest protein content was additionally analyzed by Slotblot with sera of patients' allergies, among others, to soy (Figure 4).…”
Section: Discussionmentioning
confidence: 99%